Social networking sites: Tools that enhance learning activites among the postgraduate students / Alkasim Haruna - Haruna, Alkasim (Universiti Teknologi MARA, Kedah, 2019)
Social networking sites are increasingly becoming an important tool that enhances the study of English language. Despite its extraordinary growth in the everyday life of user’s education, documented evidences have shown various studies on (SNS) as the dominant theme in the academic cycle of researchers, teachers, language educators and students. However, many studies have conducted on the application SNS to enhance the teaching and learning of English language in the classroom context. Such as; WhatsApp, Twitter, Facebook, www.englishbaby.com, You Tube and Instagram. This study aims to investigate how social media sites can improve research activities and English language skills among Nigerian students studying at Universiti Utara Malaysia. Research participants were 10 postgraduates and undergraduates’ students. Data was generated through face-to-face interviews and was transcribed verbatim. The analysis of data was conducted using thematic analysis. The findings showed that five main categories of themes were emerged from the participants views and ideas on the effectiveness and impact of integrating social networking sites for teaching English language. The study also finds that WhatsApp, Face book and You Tube are the most common social media site that they prefer most. Finally, the paper suggested that social networking sites can be incorporated in the syllabus to improve English language teaching and learning.